2021
DOI: 10.3390/ph14010049
|View full text |Cite
|
Sign up to set email alerts
|

Modifications on the Tetrahydroquinoline Scaffold Targeting a Phenylalanine Cluster on GPER as Antiproliferative Compounds against Renal, Liver and Pancreatic Cancer Cells

Abstract: The implementation of chemo- and bioinformatics tools is a crucial step in the design of structure-based drugs, enabling the identification of more specific and effective molecules against cancer without side effects. In this study, three new compounds were designed and synthesized with suitable absorption, distribution, metabolism, excretion and toxicity (ADME-tox) properties and high affinity for the G protein-coupled estrogen receptor (GPER) binding site by in silico methods, which correlated with the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Interestingly, both ligands largely share the same binding mode on GPER binding site (Fig. 2 A), reaching entirely the phenylalanine cluster formed by Phe206, Phe208, Phe223, and Phe278, described as key orchestrator of the GPER activity 28 . Additionally, the subtle differences among both binding modes lie in the presence of Gln215 establishing a h-bond with one of the oxygen atoms from the sulfonamide moiety of 6 at a close contact of 3.11 Å (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, both ligands largely share the same binding mode on GPER binding site (Fig. 2 A), reaching entirely the phenylalanine cluster formed by Phe206, Phe208, Phe223, and Phe278, described as key orchestrator of the GPER activity 28 . Additionally, the subtle differences among both binding modes lie in the presence of Gln215 establishing a h-bond with one of the oxygen atoms from the sulfonamide moiety of 6 at a close contact of 3.11 Å (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…On the chemical basis of a GPER pharmacophore composed of a tetrahydroquinoline scaffold, we previously developed a GPER ligand named G1-PABA 26 28 which contains in its structure a carboxylic acid group capable of being modified by an amide bond formation. Taking advantage of that, we proposed functionalizing it by forming an amide bond with nucleophilic amines, which contain chemical moieties in its structure, capable of reaching the Bcl-2 binding site 29 , 30 and, consequently, blocks both GPER and Bcl-2 aberrant activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, emerging in silico data are beginning to uncover the molecular mechanism of GPER-ligand interactions. A phenylalanine cluster at the GPER active site is essential for GPER recognition by its agonists and antagonists and this molecular scaffold is proposed to be the binding site of some synthetic tetrahydroquinoline derivatives that inhibit the proliferation of human renal, liver, and pancreatic cancer cell lines in vitro [150]. The finding thus provides insight into the potential role of GPER in the pharmacological treatment of these cancers.…”
Section: Gper Signaling In Renal Liver and Pancreatic Cancermentioning
confidence: 99%
“…With this study, the authors introduce a novel system which can also be used as a future tool in sense-checking newly resolved structures and planning experimental design. The work by Mendez-Luna and coworkers [3] is a joint investigation combining computational tools and experimental assays in order to design potential drug candidates inhibiting the G protein-coupled estrogen receptor (GPER). Under this context, the authors design three compounds that showed notable inhibitory activity against GPER when tested in nonconventional cell models.…”
mentioning
confidence: 99%